PipaBot: um canal de comunicação para o PIPA UFRJ - Paula, Lucas S. de; Gonçalves, Taisa G.; Fernandes, Thatiana V. R. B.; Travassos, Guilherme H. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
Chatbots make use of natural language processing to establish dialogues with people. They can be used as channels that facilitate communication between humans and entities (companies, social projects, research projects, hospitals, schools/universities, etc.). The PipaBot is a chatbot that was built to facilitate the communication between the mothers (expected two thousand participants) and researchers from the Childhood and Environmental Pollutants Project (PIPA-UFRJ). It was built following an incremental and iterative way and used the Botpress framework. The chatbot is available in two versions: Facebook Messenger and PIPA-UFRJ website. The actions provided by PipaBot are (i) registration of a project participant; (ii) information about the project, medical consultations, and result of medical exams, among others. The PipaBot was evaluated following the Technological Acceptance Model (TAM) with 13 participants, and the initial results provided evidence of user satisfaction regarding its acceptance.